Analysis of Nurse Competency in Implementing SDKI, SIKI, and SLKI - Based Nursing Care at Aji Muhammad Parikesit Regional General Hospital, Tenggarong,East Kalimantan - Rahayu, Anik Puji; Rahmadhani, Siti; Fransiska, Novia; Riko, Riko (Fakultas Kedokteran, 2024)
Background: Competence of Indonesian nurses as caregivers using the 3S Nursing Care Standard (PPNI, 2013). Method: This study is a quantitative study with a Cross-sectional research design. Bivariate analysis using the Chi-Square Test and Multivariate Analysis using the Logistic Regression Test to analyze the most influential factors on nurse competence in implementing the 3S nursing care. Results: the majority of nurses are 20-30 years old, 77 respondents (67%). Age 31-40 years 33 respondents (28.7%) and Age 41-50 years 5 respondents (4.3%). Education level D3 as many as 63 respondents (54.8%), Nurses as many as 52 respondents (45.2%). A total of 85 respondents (71.3%) were at level PK 1, 27 respondents (23.5%) were at level PK 2, and 6 respondents (5.2%) were at level PK 3. Length of work of nurses 78 people with a work period of 1-5 years (67.8%), a work period of 6-10 years 30 respondents (26.1%) and 10-15 years there were 7 respondents (6.1%). Moderate knowledge 83 respondents (72.1%), 18 respondents had good knowledge (15.8%) and 14 people had poor knowledge (12.1%). Good motivation as many as 64 respondents (56%), moderate motivation 50 respondents (43.3%) and poor motivation 1 respondent (0.7%). Heavy workload as many as 64 respondents (55.7%), 41 respondents (36.7%) moderate workload and 10 respondents (7.6%) said light workload. Rewards and punishments were good as many as 102 respondents (88.7%), 13 respondents (11.3%) rewards and punishments were lacking. 6 rooms obtained data from Enggang 1 room which had the highest value with a percentage of 91%. The relationship between nurses' knowledge. Motivation and workload were related to the implementation of 3S nursing care (P-Value 0.000), while rewards and punishments (P-value 0.35>α=0.05) had no relationship with the implementation of 3S nursing care. The most influential factors in the implementation of nursing care were knowledge, motivation and workload based on the logistic regression test (P-value 0.000). Based on the results of this study, it is necessary to increase knowledge of 3S nursing care, increase work motivation and review the effective and efficient workload of nurses and broader research related to the implementation of nursing care.